The downregulation of NCRUPAR is associated with the clinical characteristics of hepatocellular carcinoma - Zhang, Lufei; Zhang, Yuan; He, Tianyu; Kong, Yang; Zhao, Xinyi; Huang, Yu; Xie, Haiyang; Zhou, Lin; Zheng, Shusen; Wang, Weilin (Translational Cancer Research; Vol 6, No 2 (April 28, 2017): Translational Cancer Research, 2017)
Background: Long non-coding RNAs (lncRNAs) appear to be a new class of regulators of cellular processes, such as cell growth, apoptosis, and carcinogenesis. However, the clinical significance of most lncRNAs in screening for hepatocellular carcinoma (HCC) is largely unknown. Recently, a novel lncRNA upstream from the coagulation factor II thrombin receptor (F2R/PAR1) gene, called NCRUPAR, was found to be involved in the tumorigenesis of colorectal cancer and gastric cancer. However, the expression of NCRUPAR and its clinical significance in HCC have not yet been reported. Methods: We collected 137 samples of HCC tissues compared with paired adjacent nontumor tissues and measured the NCRUPAR levels in tissues and cell lines using real-time reverse transcription-polymerase chain reaction, and then the associations between NCRUPAR expression and the clinicopathological features of HCC. Results: The expression of NCRUPAR in the HCC cell lines HCCLM3, HUH7, MHCC97H, SK-Hep1 and Hep3B was significantly downregulated compared with the normal liver cell line QSG-7701. It was downregulated in 73.7% (101/137) of the HCC tissues compared with paired adjacent normal tissues (P